The interface between liturgy and moral decision-making in defiance of cognitive distortions that underlie corruption: - Kruger, Ferdi Petrus (Stellenbosch Theological Journal, 2022)
The central theme of the present argument is the matter of church participants' engagement in liturgy and how this could enhance their capacity for making moral decisions. First, one should acknowledge that participants in the liturgy and faith communities have to cope with the reality that people should make moral decisions within the public domain. Liturgy has inevitably enabled participants to see things they do not or may not want to. The functioning of cognitive distortions in corruption is evident in systemic political corruption and micro-levels of community and culture. Furthermore, people are confronted with different kinds of understandings about corruption. In this article, it is argued that moral decision-making should be enhanced and communicated by liturgy. It embarks on descriptive, systemising, and strategizing perspectives to delineate faith communities' responsibility regarding people's duty to act morally within their environments. First, this article offers a descriptive section of the currently concerning aspects to be found under this rubric. Second, systemising perspectives based on the philosophy of religion and cognitive psychology are examined as centred on the intimate interplay with ethics and liturgy. Finally, the following research question is formulated and briefly discussed: Could participation in the liturgy offer a new understanding to people confronted with moral decision-making in a praxis of cognitive corruption? The methodological approach of Browning has been carefully identified to arrange the research into coherent phases and reflect on the research question. Contribution: The article concludes with one or two practical theological perspectives that could lead to a follow-up discussion around how cognitive corruption could be addressed within a liturgical praxis.